Application of Focus Variation Microscopy and Dissolution Imaging in Understanding the Behaviour of Hydrophilic Matrices - Adam Ward; Benedict Brown; Karl Walton; Peter Timmins; Barbara R. Conway; Kofi Asare-Addo (MDPI AG, 2020)
Hydrophilic matrix systems can be found in a wide range of extended release pharmaceutical formulations. The main principle of these systems is that upon contact with water, the hydrophilic component swells to form a hydrated gel layer which controls drug release. The following work demonstrates an explorative study into the use of dissolution imaging and focus variation microscopy with hydrophilic polymers. This study investigated the surface properties of xanthan gum (XG), polyethylene oxide (PEO), and hypromellose (hydroxypropyl methylcellulose, HPMC) compacts with each of these three hydrophilic polymers from one of each classification of natural, semi-synthetic, or synthetic polymer using a focus variation instrument. The auto correlation length (Sal) showed all surface profiles from the compacts displayed a value below 0.1 mm, indicating that only high frequency components (i.e., roughness) were considered and that the analysis had been successful. The developed interfacial area ratio (Sdr) displayed values below 5% in line with ISO guidelines for all the polymers studied with their texture aspect ratio values (Str) > 0.5, indicating uniformity of the surfaces of the produced compacts. Of the various parameters studied, areal material ratio (Smr2) predicted XG to wet and hydrate quicker than PEO, with PEO also wetting and hydrating quicker than the HPMC. The dissolution imaging and initial swelling studies proved to concur with the findings from the areal material ratio (Smr2) parameter, suggesting porosity was not an indicator for the ease with which water ingress occurs. This study suggests the Smr2 surface parameter to potentially predict wetting and initial hydration of hydrophilic polymers, however care should be taken as this study consists of a selected number of hydrophilic polymers.